Economic evaluations of system-based obesity interventions: the case for a new approach - Sonntag, Diana; Sweeney, R.; Litaker, David; Moodie, M. (Obesity reviews, 2018)
System-based interventions are of increasing interest as they seek to modify environments (e.g. socio-cultural system, transport system or policy system) that promote development of conditions such as obesity and its related risk factors. In our commentary, we draw attention to features of the system-based approach that may explain the relative absence of economic evaluations of the cost-effectiveness of these interventions, needed to guide decision-making on which to deploy. We present and discuss potentially applicable methods and alternative approaches based on our experiences in two major system-based interventions currently underway (in Melbourne, Australia and Gaggenau, Germany) that begin to fill this gap. We feel the issues and potential solutions outlined in this commentary are important for a broad range of stakeholders (e.g. clinicians, interventionalists, policy makers) to consider as they seek to address the issue of obesity.
Gesehen am 30.03.2020